Photosynthetic Acclimation in Pea and Soybean to High Atmospheric CO2 Partial Pressure. - Xu, D. Q. (1994)
Nonnodulated pea (Pisum sativum L. cv Frosty) and soybean (Glycine max [L.] Merr. cv Wye) plants were grown under artificial lights from germination with ample nutrients, 600 [mu]mol photons m-2 s-1, and either 34 to 36 (control) or 64 to 68 Pa (enriched) CO2. For soybean, pod removal and whole-plant shading treatments were used to alter the source-sink balance and carbohydrate status of the plants. Growth of both species was substantially increased by CO2 enrichment despite some down-regulation of photosynthesis rate per unit leaf area ("acclimation"). Acclimation was observed in young pea leaves but not old and in old soybean leaves but not young. Acclimation was neither evident in quantum yield nor was it related to triose phosphate limitation of net photosynthesis. A correlation between levels of starch and sugars in the leaf and the amount of acclimation was apparent but was loose and only weakly related to the source-sink balance of the plant. A consistent feature of acclimation was reduced ribulose bisphosphate carboxylase (RuBPCase) content, although in vivo RuBPCase activity was not necessarily diminished by elevated growth CO2 owing to increased percentage of activation of the enzyme. A proposal is discussed that the complexity of photosynthetic acclimation responses to elevated CO2 is as an expression of re-optimization of deployment of within-plant resources at three levels of competition.